Wage Disparities Across Caste Groups in Nepal’s Labor Market - Panthi, Hemanta (Journal of Emerging Management Studies, 2025)
Purpose – This study examines wage disparities across caste groups in Nepal’s labor market, focusing on whether these differences arise from human capital endowments or structural discrimination. Design/methodology/approach – Using data from the National Labor Force Survey (NLFS) 2017/18, this paper employs the Oaxaca-Blinder decomposition method to separate wage differentials into explained and unexplained components, identifying the role of education, experience, and other market-related factors. Findings and Conclusion – The results indicate that caste-based wage gaps are largely driven by differences in education, experience, and other human capital factors rather than direct wage discrimination. However, lower returns to education for marginalized caste groups suggest the presence of structural barriers that persist in Nepal’s labor market. Implications – This study underscores the need for inclusive labor policies and targeted skill development programs to reduce caste-based economic disparities. Originality/value – By applying the Oaxaca-Blinder decomposition to caste-based wage differentials, this paper provides new insights into the structural challenges affecting Nepal’s labor market and contributes to policy discussions on labor inclusion.